Vascular hyperpolarization to β-adrenoceptor agonists evokes spreading dilatation in rat isolated mesenteric arteries. - Garland, C; Yarova, P; Jiménez-Altayó, F; Dora, K (2011)
BACKGROUND AND PURPOSE: β-Adrenoceptor stimulation causes pronounced vasodilatation associated with smooth muscle hyperpolarization. Although the hyperpolarization is known to reflect K(ATP) channel activation, it is not known to what extent it contributes to vasodilatation. EXPERIMENTAL APPROACH: Smooth muscle membrane potential and tension were measured simultaneously in small mesenteric arteries in a wire myograph. The spread of vasodilatation over distance was assessed in pressurized arteries following localized intraluminal perfusion of either isoprenaline, adrenaline or noradrenaline. KEY RESULTS: Isoprenaline stimulated rapid smooth muscle relaxation associated at higher concentrations with robust hyperpolarization. Noradrenaline or adrenaline evoked a similar hyperpolarization to isoprenaline if the α(1)-adrenoceptor antagonist prazosin was present. With each agonist, glibenclamide blocked hyperpolarization without reducing relaxation. Focal, intraluminal application of isoprenaline, noradrenaline or adrenaline during block of α(1)-adrenoceptors evoked a dilatation that spread along the entire length of the isolated artery. This response was endothelium-dependent and inhibited by glibenclamide. CONCLUSIONS AND IMPLICATIONS: Hyperpolarization is not essential for β-adrenoceptor-mediated vasodilatation. However, following focal β-adrenoceptor stimulation, this hyperpolarization underlies the ability of vasodilatation to spread along the artery wall. The consequent spread of vasodilatation is dependent upon the endothelium and likely to be of physiological relevance in the coordination of tissue blood flow.